2001
DOI: 10.1525/can.2001.16.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Civic Virtue and Religious Reason: An Islamic Counterpublic

Abstract: Since the rise of modernization theory in the 1960s up through present concerns with globalization, a growing body of anthropological and sociological scholarship has explored the impact of modern media technologies on religious practice. Scholars have frequently approached this topic in terms of a polarity between what are assumed to be two contradictory processes: the deliberative and the disciplinary. Analyses focusing on the deliberative aspect have emphasized the possibilities of argument, contestation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(58 citation statements)
references
References 8 publications
0
54
0
4
Order By: Relevance
“…In my earlier work, I discussed the emergence in Egypt of what I called "an Islamic counterpublic" (Hirschkind 2001(Hirschkind , 2006. Articulated by the wide circulation of popular cassette-recorded sermons among the lower and lower-middle classes in Cairo, this public arena connects Islamic ethical traditions to practices of deliberation about the common good, the duties of Muslims in their status as national citizens, and the future of the greater Islamic community.…”
Section: Sensory Politicsmentioning
confidence: 99%
“…In my earlier work, I discussed the emergence in Egypt of what I called "an Islamic counterpublic" (Hirschkind 2001(Hirschkind , 2006. Articulated by the wide circulation of popular cassette-recorded sermons among the lower and lower-middle classes in Cairo, this public arena connects Islamic ethical traditions to practices of deliberation about the common good, the duties of Muslims in their status as national citizens, and the future of the greater Islamic community.…”
Section: Sensory Politicsmentioning
confidence: 99%
“…Hence with my interlocutors it is apparent that they saw this kind of participation in events such as the kermes as not only an act of charity and fund raising but, like piety, it is a commitment in every aspect of life to a greater meaning. In many studies, anthropologists refer to religious practices as main constituents of the moral self (Mahmood 2005;Hirschkind 2001), but in my ethnography I have found that even the mundane conduct can be a method of moral construction, if the person doing it bears the consciousness of investing time and effort for God's disposition.…”
Section: Enchanted Language and Disenchanted Practicementioning
confidence: 95%
“…The emergence of new media in the dissemination of religious ideas changes the character of religiosity because it empowers different social actors and increases access to religious knowledge, which result in a "fragmentation of authority" (Eickelman and Anderson 1999). For instance, using the new technology of CDs transformed the methods for cultivating the pious self through listening to religious poetry (Eisenlohr 2006) or listening to taped sermons challenging the reason-based public sphere (Hirschkind 2001). However, this article analyzes how rituals, as media of representation, impact the content of the Islamic message and the social organization of the community.…”
mentioning
confidence: 99%